Classification and Assessment the Composition of Plastic Waste Drived from Household Product on Nhue River, from Chem Drain to Noi Bridge - Huong, Tran Thi Thu; Xuan Tong, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2022)
This study is carried out for the purpose of collection, classification and assessment plastic waste component by household product origin. Survey results from 9/2020 to 01/2021 along the two banks of Nhue river, from Chem drain to Noi bridge showed that there is a clear difference between areas, the plastic waste appears depending on living habits, population characteristics and frequency/quantity of plastic products used by households. Six types of plastic PP, PET, HDPS, LDPE, PS-E, PVC appeared in 10 sampling areas with different quantities, weights and absent of the products derived from PS. The PET plastic group appeared with the highest number of 327 pieces with the weight of 1678.73 g and the lowest number was HDPE plastic with 44 pieces, but the lowest weight was recorded in the PP plastic group with 726.08 g. Size classification indicated that the number and weight of plastic pieces in different sizes are not proportional to each other. The weight of plastic pieces with size of 20-50 cm accounts for the majority of all the sampling areas, KV01 has the largest value accounting for 73.95% and the lowest is KV04 with 16.76%. The size of plastic pieces 0-<5 cm appears with a relatively low rate ranging from 0.01 to 6.35%, KV09 does not appear plastic pieces with this size. The remaining sizes including: 5-<10; 10-<15; 15-<20; 20-<50 and 50-1000 cm appear with the lowest rate of 1.88% (KV01, size of 50-1000 cm) to the highest of 52.17% (KV08, size of 15-<20 cm). The study results also show that people's living habits and demand for plastic products have a great influence on the distribution of plastic waste along the two banks of the river. Therefore, the community counseling/media programs for raising awareness of the people about the harmful effects of plastics and related products from plastic need to supplement.